Cutaneous manifestations of pediatric lupus. Issue 5 (September 2019) - Arkin, Lisa M.; Nguyen, Cordellia; Klein-Gitelman, Marisa
Abstract : Purpose of review: To review recent evidence on cutaneous manifestations of lupus, with a focus on evidence for pediatric patients. Recent findings: Cutaneous manifestations of SLE are common and may precede signs or symptoms of systemic disease. Early recognition and initiation of therapy improves quality of life by reducing cutaneous disease activity. Antimalarials are first line for moderate-to-severe disease. Photo protection is a critical component of therapy and perhaps the only modifiable risk factor for SLE. Recognition of cutaneous vasculopathy may reduce mortality from vascular occlusion. Summary: There is a critical need for better understanding of pathogenesis, risk factors and outcomes in cutaneous lupus to determine optimal treatment and surveillance strategies. Correlation of clinical phenotypes with biomarkers may help to stratify patients, optimize targeted interventions, and influence prognosis.